BIOCIDAL POTENTIALS OF STEM BARK EXTRACTS OF PSIDIUM GUAJAVA (LINN.) ON PANEL OF BACTERIAL STRAINS ASSOCIATED WITH DIARRHEA AND DYSENTERY - RASHEEDAT ABIDOYE, OLADAYO; AYINDE AKINPELU, DAVID; ALAYANDE, KAZEEM ADEKUNLE; OLADELE AGUNBIADE, MAYOWA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Investigations were carried out on cidal effects of crude extract and fractions obtained from stem bark of Psidium guajava against a panel of 74 strains of Escherichia coli and Shigella dysenteriae implicated in diarrhea and dysentery infections. Methods: Powdered sample of the stem bark was extracted in methanol/distilled water (3:2) and then partitioned into different organic solvents. The fractions obtained were subjected to antibacterial tests against a panel of bacterial strains. The minimum inhibitory concentrations (MIC) and minimum bactericidal concentrations (MBC) were determined using agar dilution method while the mode of action of the active fractions was investigated through time-kill dynamics and leakages of proteins and potassium ions from the cells. Results: All partitioned fractions except the aqueous fraction exhibited antibacterial activities against the panel of bacterial strains at a final concentration of 10 mg/mL. The MIC exhibited by the crude extract against susceptible bacterial strains ranged between 1.56 mg/mL and 12.5 mg/mL, while the MIC for the four fractions ranged between 0.31 mg/mL and 5.0 mg/mL. The MBC ranged between 3.13–12.5 mg/mL and 0.63–5.0 mg/mL for the crude extract and fractions, respectively. The time-kill assay revealed that the percentage of the cells killed increase with an increase in the concentrations of the fractions as well as contact time intervals. Proteins and potassium ions leakages from the bacterial cells followed the same trend with that of time-kill assay. Conclusion: The stem bark extracts of P. guajava exhibited appreciable bactericidal effects on bacterial strains associated with diarrhea and dysentery in humans.